PENGEMBANGAN KEGIATAN KEAGAMAAN DI MADRASAH ALIYAH DALAM MENINGKATKAN SPIRITUALITAS DAN MORAL SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the development of religious activities in Madrasah Aliyah in enhancing students’ spirituality and moral character. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving school principals, Islamic education teachers, religious activity supervisors, and students as research subjects. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation.The results indicate that the development of religious activities is implemented in a structured manner through daily, weekly, and annual programs, which not only focus on ritual aspects but also emphasize character building and social development. The development strategies include habituation of religious practices, teacher role modeling, active student participation, and the use of varied and contextual learning methods. These developments have a significant impact on improving students’ spirituality, as reflected in increased awareness of worship, closer relationship with God, and the internalization of religious values in daily life. Furthermore, religious activities also contribute to the improvement of students’ moral behavior, including discipline, responsibility, politeness, and social awareness.However, several challenges were identified, such as low student interest, the influence of technological developments, and limited facilities and infrastructure. Therefore, innovation in developing religious activities is needed to ensure they remain adaptive and relevant to the needs of students in the modern era.